Discussing economics : a classroom guide to preparing discussion, questions and leading discussion - Salemi, Michael K.; Hansen, W. Lee. (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2005)
This book explain why instructors should organize discussion around interpretive questions, how to plan and lead discussion, and how to integrate it into a course. They then provide a guide to over 60 classic and contemporary readings that span much of the undergraduate economics curriculum. For each, they provide a synopsis, learning objectives, recommended questions, and discussion suggestions.
Includes bibliographical references (p. 287-290) and index.
gau 24/01/14
Loans
Keywords: Economics - studing and teaching; Microeconomics - discussion; Macroeconomics - discussion; Financial economics - discussion